Building bots with Microsoft Bot Framework : build intelligent and smart conversational interfaces using Microsoft Bot Framework - Gaddam, Kishore (Packt Publishing, 2017)
Build intelligent and smart conversational interfaces using Microsoft Bot Framework About This Book Develop various real-world intelligent bots from scratch using Microsoft Bot Framework Integrate your bots with most popular conversation platforms such as Skype, Slack, and Facebook Messenger Flaunt your bot building skills in your organization by thoroughly understanding and implementing the bot development concepts such as messages (rich text and pictures), dialogs, and third-party authentication and calling Who This Book Is For This book is for developers who are keen on building powerful services with great and interactive bot interface. Experience with C# is needed. What You Will Learn Set up a development environment and install all the required software to get started programming a bot Publish a bot to Slack, Skype, and the Facebook Messenger platform Develop a fully functional weather bot that communicates the current weather in a given city Help your bot identify the intent of a text with the help of LUIS in order to make decisions Integrate an API into your bot development Build an IVR solution Explore the concept of MicroServices and see how MicroServices can be used in bot development Develop an IoT project, deploy it, and connect it to a bot In Detail Bots help users to use the language as a UI and interact with the applications from any platform. This book teaches you how to develop real-world bots using Microsoft Bot Framework. The book starts with setting up the Microsoft Bot Framework development environment and emulator, and moves on to building the first bot using Connector and Builder SDK. Explore how to register, connect, test, and publish your bot to the Slack, Skype, and Facebook Messenger platforms. Throughout this book, you will build different types of bots from simple to complex, such as a weather bot, a natural speech and intent processing bot, an Interactive Voice Response (IVR) bot for a bank, a facial expression recognition bot, and more from scratch. These bots were designed and developed to teach you concepts such as text detection, implementing LUIS dialogs, Cortana Intelligence Services, third-party authentication, Rich Text format, Bot State Service, and microServices so you can practice working with the standard development tools such as Visual Studio, Bot Emulator, and Azure. Style and approach This step-by-step guide takes a learn-while-doing approach, delivering the practical knowledge and experience you need to design and build real-world Bots. The concepts come to you on an as-needed basis while developing a bot so you increase your programming knowledge and experience at the same time.